2018
DOI: 10.1186/s13045-018-0570-z
|View full text |Cite
|
Sign up to set email alerts
|

Immunoregulatory functions and the therapeutic implications of GARP-TGF-β in inflammation and cancer

Abstract: GARP (glycoprotein-A repetitions predominant) is a type I transmembrane cell surface docking receptor for latent transforming growth factor-β (TGF-β) that is abundantly expressed on regulatory T lymphocytes and platelets. GARP regulates the availability of membrane-bound latent TGF-β and modulates its activation. For this reason, GARP expression on immune and non-immune cells is involved in maintaining peripheral tolerance. It plays an important role in preventing inflammatory diseases such as allergy and graf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
64
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(67 citation statements)
references
References 101 publications
3
64
0
Order By: Relevance
“…The function of GARP is to activate latent TGF-β in the close proximity of platelets. The GARP-TGFβ complex together with platelet-secreted lactate inhibited T cell immunity against both melanoma and colon cancer [ 42 , 43 ]. These data substantiate the notion that platelets interfere with the innate as well as with the adaptive immune system to tackle cancer cells.…”
Section: Role Of Platelets In Cancer Metastasismentioning
confidence: 99%
“…The function of GARP is to activate latent TGF-β in the close proximity of platelets. The GARP-TGFβ complex together with platelet-secreted lactate inhibited T cell immunity against both melanoma and colon cancer [ 42 , 43 ]. These data substantiate the notion that platelets interfere with the innate as well as with the adaptive immune system to tackle cancer cells.…”
Section: Role Of Platelets In Cancer Metastasismentioning
confidence: 99%
“…13). The release of the biologically active mature TGFb from this complex can occur by several factors including heat, acidic conditions, and integrins (14). Earlier reports have shown that GARP-deficient CD4 þ T cells mice did not impair the suppressive function of Treg cells in vitro (15) and that silencing of its expression by RNA interference does not significantly affect Foxp3 expression in expanded Tregs (16).…”
Section: Introductionmentioning
confidence: 99%
“…Robust anti-cancer immune response consists of a series of stepwise immune events including the release of cancer-associated antigens, the processing and presentation of antigen presentation cells (APCs), the priming and activation of naïve T cells, the trafficking and migration of activated T cells, and the tumor-killing activity of effector cells [1,2]. Actually, the anti-cancer immune response is a highly complex process which could be strengthened or weakened by multiple factors such as immune editing, transforming growth factor-β (TGF-β) signaling, and immune checkpoints [3][4][5]. The balance between immunostimulatory and -inhibitory factors is crucial to maintain the immune homeostasis of host and clear the cancerderived materials [6].…”
Section: Introductionmentioning
confidence: 99%